Integration of high and low field 1H NMR to analyse the effects of bovine dietary regime on milk metabolomics and protein-bound moisture characterisation of the resulting mozzarella cheeses during ripening. (April 2019) - Boiani, Mattia; Sundekilde, Ulrik; Bateman, Lorraine M.; McCarthy, Daniel G.; Maguire, Anita R.; Gulati, Arunima; Guinee, Timothy P.; Fenelon, Mark; Hennessy, Deirdre; FitzGerald, Richard J.; Kelly, Phil M.
Abstract: The influence of dairy cow feeding regime was investigated using 1 H nuclear magnetic resonance (NMR). Two different NMR analytical systems were deployed: high field 1 H NMR to investigate the influence on milk metabolomics and low field NMR to characterise proton relaxation linked to changes in the state of mozzarella cheese moisture during ripening. The metabolomics results showed that grass-based feeding increased the concentration of a biological marker that signifies near-organic milk production conditions. On the other hand, the investigation of cheese moisture distribution showed that grass-based diets reached final moisture partitioning in a shorter time, which implied the formation of a more compact protein structure in the cheese matrix. These results indicate that pasture-based dairying may be differentiated in terms of the provenance of milk produced along with the accrual of additional benefits during ripening of the resulting mozzarella cheeses.